Benchmarking Mentorship: Creating and Validating a Quality Scale for ELT Mentors - Ali Kondori; Mitra Zeraatpishe; Hamid Ashraf; Khalil Motallebzadeh (Research in English Language Pedagogy)
In the context of language teaching, mentorship can be a valuable tool to support the ongoing professional development of language teachers, improving the quality of language teaching and learning and fostering a sense of community within the teaching profession. Therefore, it is crucial to identify the qualities that characterize a good mentor. This study aimed to develop and validate a Good Mentor Qualities (GMQ) scale for use in L2 educational contexts. The study employed a qualitative research design with a quasi-experimental component, which was of a qualitative nature. It involved the use of structured interviews and observations to explore the Iranian EFL teachers’ opinions about the qualities of a good mentor in Iran, with a particular focus on evaluating mentors.  The sample consisted of 10 experienced EFL teachers and 100 novice EFL teachers teaching at various private language institutes. Semi-structured interviews were conducted by the researcher with the mentors and mentees, each lasting approximately 30 minutes to gather data. Five interview questions were developed based on a list of 10 themes. The interviews elicited the participants’ perspectives and opinions regarding the requirements good mentors need to meet in an ELT context. Based on this interview, relevant constructs were extracted, patterns were identified, and items were determined. The transcription of the recorded interview followed this. Then, the transcribed data were interpreted in light of existing literature. Ultimately, the data were analysed using NVivo software. Based on the data extracted, a Good Mentor Qualities (GMQ) scale was developed. The results of the Rasch rating scale model and Cronbach’s alpha indicated that the developed questionnaire had satisfactory validity and reliability indices. The GMQ scale can serve as a valuable tool for evaluating and selecting mentors, as well as for assessing the effectiveness of mentorship programs. The results are discussed, and further applications for EFL teachers and learners are explored.